2016
DOI: 10.3390/ijms17111746
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Pr130 Interrupts Cardiac Development in Zebrafish

Abstract: Protein phosphatase 2 regulatory subunit B, alpha (PPP2R3A), a regulatory subunit of protein phosphatase 2A (PP2A), is a major serine/threonine phosphatase that regulates crucial function in development and growth. Previous research has implied that PPP2R3A was involved in heart failure, and PR130, the largest transcription of PPP2R3A, functioning in the calcium release of sarcoplasmic reticulum (SR), plays an important role in the excitation-contraction (EC) coupling. To obtain a better understanding of PR130… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…). These abnormalities have been associated with a broad variety of conditions including, as examples, rearing systems for Eurasian perch, Perca fluviatilis (Alix et al, ), larval rearing temperatures for Atlantic halibut, Hippoglossus hippoglossus L. (Ottesen & Bolla, ), embryo cryopreservation practices for streaked prochilod, Prochilodus lineatus (Costa, de Souza, Senhorini, Veríssimo‐Silveira, & Ninhaus‐Silveira, ), and, in zebrafish, phenanthroline toxicity (Ellis & Crawford, ), influenza A virus infection (Gabor et al, ), knockdown or KO of genes related to kidney function or development, respectively (Hanke et al, ; Zhang et al, ), knockdown of the wwox tumor suppressor gene (Tsuruwaka, Konishi, & Shimada, ), deletion of a gene ( pr130 ) encoding a protein essential for myocardium formation and cardiac contractile function (Yang et al, ), and mutagenesis of genes involved in thyroid morphogenesis and function (Trubiroha et al, ), among others. The edemas may ultimately result from many different proximal causes such as cardiac, kidney, liver, or osmoregulatory failure, and researchers are just beginning to develop screens to differentiate between them (Hanke et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…). These abnormalities have been associated with a broad variety of conditions including, as examples, rearing systems for Eurasian perch, Perca fluviatilis (Alix et al, ), larval rearing temperatures for Atlantic halibut, Hippoglossus hippoglossus L. (Ottesen & Bolla, ), embryo cryopreservation practices for streaked prochilod, Prochilodus lineatus (Costa, de Souza, Senhorini, Veríssimo‐Silveira, & Ninhaus‐Silveira, ), and, in zebrafish, phenanthroline toxicity (Ellis & Crawford, ), influenza A virus infection (Gabor et al, ), knockdown or KO of genes related to kidney function or development, respectively (Hanke et al, ; Zhang et al, ), knockdown of the wwox tumor suppressor gene (Tsuruwaka, Konishi, & Shimada, ), deletion of a gene ( pr130 ) encoding a protein essential for myocardium formation and cardiac contractile function (Yang et al, ), and mutagenesis of genes involved in thyroid morphogenesis and function (Trubiroha et al, ), among others. The edemas may ultimately result from many different proximal causes such as cardiac, kidney, liver, or osmoregulatory failure, and researchers are just beginning to develop screens to differentiate between them (Hanke et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…1). These abnormailites have been associated with a broad variety of conditions including, as examples, rearing systems for Eurasian perch, Perca fluviatilis (Alix et al, 2017), larval rearing temperatures for Atlantic halibut, Hippoglossus hippoglossus L. (Ottesen and Bolla, 1998), embryo cryopreservation practices for streaked prochilod, Prochilodus lineatus (Costa et al, 2017), and, in zebrafish, phenanthroline toxicity (Ellis and Crawford, 2016), influenza A virus infection (Gabor et al, 2014), knockdown or KO of genes related to kidney function or development, respectively (Hanke et al, 2013; Zhang et al, 2018), knockdown of the wwox tumor suppressor gene (Tsuruwaka et al, 2015), deletion of a gene ( pr130 ) encoding a protein essential for myocardium formation and cardiac contractile function (Yang et al, 2016), and mutagenesis of genes involved in thyroid morphogenesis and function (Trubiroha et al, 2018), among others. The edemas may ultimately result from many different proximal causes such as cardiac, kidney, liver or osmoregulatory failure, and researchers are just beginning to develop screens to differentiate between them (Hanke et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, deletion of pr130 in zebrafish resulted in cardiac developmental defects, including cardiac looping defects, reduced cardiomyocytes, disturbance of cardiac ultra-structure and decreased cardiac function [ 15 ]. Here, we show that pr72 , which has an N terminus that differ from pr130 but sharing the same C terminus, exhibited the similar phenotype in heart.…”
Section: Discussionmentioning
confidence: 99%
“…PR72 is a negative regulator of Wnt signaling pathway, while Wnt pathway plays an important role in heart development [ 14 ]. In our previous study, we found that PR130 was required for normal cardiac development [ 15 ]. Thus, we made a hypothesis that PR72 might also play a major role in heart development.…”
Section: Introductionmentioning
confidence: 99%